2003
DOI: 10.2135/cropsci2003.2162
|View full text |Cite
|
Sign up to set email alerts
|

AFLP Analyses of Genetic Diversity in Bentgrass

Abstract: Bentgrasses (Agrostis spp.) are widely occurring temperate grasses with more than 220 species that represent a vast resource for genetic improvement of turfgrass cultivars. Bentgrasses are normally outcrossing species and exhibit many ploidy levels. Difficulties in morphological characterization, which are largely subjected to environmental influences, have resulted in many synonymous species and uncertainties in phylogenetic relationships. To study the genetic diversity and relationships between bentgrass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 16 publications
5
34
0
Order By: Relevance
“…Similar results were found by Monte et al (1993) and Sharma et al (2000). Vergara and Bughrara (2003) also found that bentgrass accessions from geographically adjacent countries commonly clustered together, but those from distant locations were clustered into different groups with low similarity coefficients. The G. arboreum had been cultivated in China for over 2000 years.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were found by Monte et al (1993) and Sharma et al (2000). Vergara and Bughrara (2003) also found that bentgrass accessions from geographically adjacent countries commonly clustered together, but those from distant locations were clustered into different groups with low similarity coefficients. The G. arboreum had been cultivated in China for over 2000 years.…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that these two cultivars clustered with A. capillaris accessions PI 290708 and PI 283173 and, thus, did not support the reclassification of these cultivars. Our results were consistent with those from Amplified Fragment Length Polymorphism (AFLP) analyses which also indicated that these cultivars were properly identified as A. capillaris (Vergara and Bughrara 2003), and with isozyme analyses that showed that these two cultivars could not be differentiated from other A. capillaris accessions (Yamamoto and Duich 1994).…”
Section: Resultssupporting
confidence: 89%
“…In cluster 3, the U.S. accession PI 578528 clustered with accession PI 283173 from Czechoslovakia. These results were not surprising, because these cultivars were selected and bred from accessions that were brought into the U.S. from Europe (Vergara and Bughrara 2003). This shows that although these American cultivars had been selected for adaptation to different environmental conditions, they retained a genetic resemblance to their European ancestors.…”
Section: Resultsmentioning
confidence: 90%
“…Genetic diversity in S. scabrum Molecular markers (AFLP) have been used successfully to elucidate genetic diversity within crops and their wild relatives, and between accessions of cultivated or semi-cultivated plants from different geographical or ecological areas, and as basis for selection and for conservation of genetic diversity (Dehmer 2001;Hammer et al 2003;Lanteri and Barcaccia 2005;Mace et al 1999;Muluvi et al 1999;McGregor et al 2002;Perera et al 1998;Potokina et al 2002;Shan et al 2005;Vergara and Bughrara 2003;de Vicente et al 2005). The present study applies AFLPs to study the genetic diversity in S. scabrum and its relationship to geographical provenance, morphological differences and the possible existence of subspecies.…”
Section: Discussionmentioning
confidence: 99%